Promoting Autonomy Through Project Work - Mesa Villa, Claudia Patricia; Frodden Armstrong, María Cristina (Íkala, Revista de Lenguaje y Cultura, 2004)
This article presents teacher and learners' experience implementing project work as a strategy the authors used in an undergraduate foreign language teaching program at an important public university in Colombia. In order to find support for their view that project work is an effective approach to developing future teachers' autonomy, students who had participated in project work were interviewed and their responses were analyzed using Benson's contributions 1997, 2001 on autonomous learning,and Legutke and Thomas (1991) on project work as a framework. The authors discuss the following issues based on the students' experience: stages in the development of the project, characteristics of project work, and its relevance to developing learner autonomy. Received: 26- 05- 04 /Accepted: 07-09-04 How to reference this article: Mesa Villa, C. P. & Frodden Armstrong, M. C. (2004). Promoting Autonomy Through Project Work. Íkala. 9(1), pp. 205 – 230